Cross-infection and infection control in dentistry: Knowledge, attitude and practice of patients attended dental clinics in King Abdulaziz University Hospital, Jeddah, Saudi Arabia - Ibrahim, Nahla K. (J Infect Public Health, 2017)
The objective of the study was to determine the level of Knowledge, Attitude and Practice (KAP) of patients attended dental clinics at King Abdulaziz University Hospital (KAUH) regarding cross infections and infection control in dentistry. A cross-sectional study was conducted among 225 patients who attended the dental clinics of KAUH, Jeddah, Saudi Arabia, 2014. A standardized, confidential, anonymous, interviewing questionnaire was used. Knowledge about dental infections was assessed by 12 MCQs. The attitudes were assessed through answering seven statements on a three- point Likert scale. Patients’ self reported practices were also evaluated. Descriptive and inferential statistics were done. Results of the study revealed that 39.5%, 38.7% and 21.8% of the participants obtained poor, fair and satisfactory level of knowledge about infections and infection control in dentistry, respectively. Social media was the commonest source of information about dental infection. Participant's educational level was significantly associated with the level of knowledge about dental infection. Patients had positive attitudes towards infection control in dentistry. Regarding self-reported practice, only few participants would ask dentists about sterilization of dental instruments (9.3%), wearing face mask (13.3%) and gloves (16.4%) if they don’t do so. In conclusion, our participants had good attitudes towards infection control in dentistry. However, their knowledge and practice need improvements. Conduction of educational programs is needed through social media, mass media, schools and public places. These programs involve both patients and providers.